The Influence of Product Quality, Fashion Trends, Comfort, and Islamic Branding on Consumer Loyalty Toward Napocut Hijab Products in Aceh - Syahira Rizqa; Muhammad Ferdiananda Chadafi; Mai Simahatie (International Journal of Economics, Commerce, and Management, 2026)
This study aims to determine the effect of product quality, fashion trends, comfort, and Islamic branding on consumer loyalty toward Napocut hijab products in Aceh. The population in this study consists of all consumers of Napocut hijab products in Aceh, with a sample size of 105 individuals. The analytical method used in this research is multiple linear regression, with data processing conducted via SPSS. The results indicate that the product quality and fashion trend variables do not partially influence consumer loyalty toward Napocut hijab products in Aceh. Meanwhile, the comfort and Islamic branding variables show a partial and significant effect on consumer loyalty toward Napocut hijab products in Aceh. Simultaneously, the variables of product quality, fashion trends, comfort, and Islamic branding significantly influence consumer loyalty toward Napocut hijab products in Aceh. The correlation coefficient (R) value of 0.840 demonstrates a strong relationship between the independent variables and the dependent variable at 84%. The coefficient of determination ( ) value of 0.705 indicates that product quality, fashion trends, comfort, and Islamic branding contribute a 70.5% influence on consumer loyalty toward Napocut hijab products in Aceh, while the remaining 29.5% is explained by other variables outside this study.